2015
DOI: 10.1016/j.jenvman.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation water quality influences heavy metal uptake by willows in biosolids

Abstract: Phytoextraction is an effective method to remediate heavy metal contaminated landscapes but is often applied for single metal contaminants. Plants used for phytoextraction may not always be able to grow in drier environments without irrigation. This study investigated if willows (Salix x reichardtii A. Kerner) can be used for phytoextraction of multiple metals in biosolids, an end-product of the wastewater treatment process, and if irrigation with reclaimed and freshwater influences the extraction process. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Concentration of Ni in willow leaves in our experiments was 1-2 mg/kg. In accordance with results of other researchers it varied from 1.97 mg/kg [45], to 10 and more mg/kg [46]. Thus, our results are closer to the lowest limits of heavy metals contents in willow biomass.…”
Section: Environmental and Climate Technologiessupporting
confidence: 93%
“…Concentration of Ni in willow leaves in our experiments was 1-2 mg/kg. In accordance with results of other researchers it varied from 1.97 mg/kg [45], to 10 and more mg/kg [46]. Thus, our results are closer to the lowest limits of heavy metals contents in willow biomass.…”
Section: Environmental and Climate Technologiessupporting
confidence: 93%
“…The research shows that, compared to Rubik, Albik cleaned the substrate more effectively. Research conducted by Laidlaw et al [23] confirms that energy crops, including willow, can be used for phytoextraction of heavy metals from substrate polluted with heavy metals. The cited authors [23] showed that willow, out of all heavy metals, extracts cadmium from the substrate most efficiently.…”
Section: Balancementioning
confidence: 99%
“…Research conducted by Laidlaw et al [23] confirms that energy crops, including willow, can be used for phytoextraction of heavy metals from substrate polluted with heavy metals. The cited authors [23] showed that willow, out of all heavy metals, extracts cadmium from the substrate most efficiently. Our own research also shows that Jerusalem artichoke, as an energy crop, also efficiently extracts Cd from the substrate.…”
Section: Balancementioning
confidence: 99%
See 2 more Smart Citations